Efficiency gains from team-based coordination: large-scale experimental evidence - Francesco Feri; Bernd Irlenbusch; Matthias Sutter (Institute for the Study of Labor (IZA), 2008)
The need for efficient coordination is ubiquitous in organizations and industries. The literature on the determinants of efficient coordination has focused on individual decision-making so far. In reality, however, teams often have to coordinate with other teams. We present an experiment with 825 participants, using six different coordination games, where either individuals or teams interact with each other. We find that teams coordinate much more efficiently than individuals. This finding adds one important cornerstone to the recent literature on the conditions for successful coordination. We explain the differences between individuals and teams using the experience weighted attraction learning model.
urn:nbn:de:101:1-2008101608
Keywords: C71; 330; Coordination games; individual decision-making; team decision-making; experience-weighted attraction learning; experiment; Gruppenentscheidung; Kooperatives Spiel; Lernprozess; Wirtschaftliche Effizienz; Test